Comment on "Ipsilateral neck radiotherapy in N2b well‐lateralized tonsil cancer—Approach with caution". Issue 9 (28th June 2019) - McDowell, Lachlan; Corry, June
Abstract : See article on page 3470–3471,  in this issue